ANALISA KADAR KAFEIN PADA KOPI HITAM YANG DISAJIKAN BERDASARKAN LAMA PENYEDUHANNYA - Mardiyah, Siti (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
ANALISA KADAR KAFEIN PADA KOPI HITAM YANG DISAJIKANBERDASARKAN LAMA PENYEDUHANNYA Siti Mardiyah, S.Si., M.Kes.Prodi D3 Analis Kesehatan UM Surabaya Abstract Coffee drinking is a favorite of many that can be enjoyed at home, at the office, at home, eat and shop - food stalls. Black coffee is one of the popular types of coffee community. Coffee consumption can cause addiction. Case is due to the caffeine content of alkaloid compounds xantin. Caffeine content of its size accepted by the body hanging from the means of treatment before drinking coffee. The   longer time  submertion Coffee will make the caffeine content in the drink gets higher.Therefore, the problem formulation in this study is will the old submertion of caffeine in black coffee? The purpose of this study is to find out the influence of long penyeduhan of caffeine in black coffee. This type of research is experimental. The sample in this study is that black coffee is often consumed by people who sold at the Market Prohibition of Sidoarjo. With black coffee sample criteria are branded or not branded. Variable in this study is the independent variable while the dependent variable brewing long the caffeine content.Data collection techniques of caffeine in black coffee served by long submertion by indirect observation using a set of laboratory experiments. Inspection rate this caffeine use spectrophotometry method. And data analysis techniques used ANOVA test to find out the influence of long submertion of caffeine in black coffee with α = 0.05. Once the proceeds of caffeine in black coffee in a statistical analysis shows the value of P = 0.000 (<0.05), the obtained conclusions that received behold Ha long submertion influence on the rate of caffeine in black coffee. Was proven that there was an increase in the rate of caffeine every submertion long time has been determined. Keyword : kafein, coffee,